Analysis of genetically modified foods and consumer: 25 years of research indexed in scopus - Alvarez-Risco, Aldo (2025)
Genetically modified (GM) foods are frequently recognized as an essential source of world food supply, linked to Sustainable Development Goal (SDG) 2: Zero hunger. However, several aspects of the risks and benefits of consuming GM foods have not yet been fully clarified. It is necessary to have the most relevant information to have more accurate legislation that benefits the population. The current research aimed to develop a bibliometric analysis; it also used VOSviewer visualization software to show the evaluation of publications indexed in the Scopus database focused on GM foods and consumers between 1999 and 2023. 979 documents were evaluated. The United States was recognized as the most productive (988 articles); however, Universiteit Gent was the institution with more publications (22), and the European Commission was the funding sponsor with more publications (19). The top institutions originated are from USA, UK, China, Italy and Germany. Nature Biotechnology was the journal with more articles published (28 articles). The study allows for gathering information that helps companies to improve the supply of GM foods and help regulators to generate policies and laws according to scientific evidence.